Behaviour of under sleeper pads at switches and crossings – Field measurements. (April 2018) - Le Pen, Louis; Watson, G; Hudson, A; Powrie, W
Major growth in rail traffic in many parts of the world in recent years has brought railway networks close to capacity and restricted the time available for track access to carry out maintenance work without costly temporary route closures. There are, therefore, significant benefits in designing or modifying ballasted track systems to reduce maintenance and associated access requirements. Under sleeper pads (USPs) offer the potential to extend ballasted track system life and to extend the intervals between routine maintenance. This paper presents and evaluates field measurements, made using geophones and high speed filming with digital image correlation (DIC), of the performance of a renewed section of track incorporating two switches and crossings (S&C) over a period of two years. One S&C was fitted with two types of USP (categorised as medium and soft), while the other had no USPs and acted as a control. Measurements demonstrate that the bearers with USPs fitted showed less variability in movement than bearers without USPs fitted. The provision of soft USPs caused large increases (>40%) in vertical bearer movements relative to bearers without USPs, although the medium USPs showed little difference. Increased movements of elongated bearers supporting both tracks fitted with soft USPs led to increased bearer rotations towards the loaded track. This effect was aided by the rigid steel collar fixing in the middle of the bearer used in this design of S&C, and raises questions concerning the desirability of this feature. DIC measurements showed that the at rest position of the elongated bearers rotated towards the track on which a train had most recently passed.